2005
DOI: 10.1007/s10443-004-6138-9
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of Sandwich Composites; Effects of Core?Skin Debonding and Core Density

Abstract: Foam-core sandwich composites have been fabricated using innovative co-injection resin infusion technique and tested under in-plane compression. The sandwich construction consisted of Klegcell foam as core materials and S2-glass/vinyl ester composites as face sheets. Tests were conducted with various foam densities and also with implanted delamination between the core and the face sheet. The intent was to investigate the effect of core density, and the effect of core-skin debonds on the overall buckling behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The results showed that the structure with the highest core density (the closest to the face sheet density) had minimal delamination propagation. This showed that less abrupt density transition will lessen the likelihood of delamination (Mahfuz et al, 2004). Thus, it is much preferred that the scaffold functional gradients should avoid discrete gradient as much as possible.…”
Section: Spatial Gradients Of Fgsmentioning
confidence: 93%
“…The results showed that the structure with the highest core density (the closest to the face sheet density) had minimal delamination propagation. This showed that less abrupt density transition will lessen the likelihood of delamination (Mahfuz et al, 2004). Thus, it is much preferred that the scaffold functional gradients should avoid discrete gradient as much as possible.…”
Section: Spatial Gradients Of Fgsmentioning
confidence: 93%
“…First the results are validated for the case of sandwich structures without attached mass. Mahfuz and Seifulislam [15] calculated the buckling load of sandwich panels with three different foam core materials experimentally. Three layers of plane weave S2 glass fibers were used in each face sheet.…”
Section: Resultsmentioning
confidence: 99%
“…The material properties and the dimensions of the panel are listed in Tables 1 and 2, respectively. Table 3 presents the results of the present model versus the experimentally calculated buckling loads in Mahfuz and Seifulislam [15].…”
Section: Overview Of the Finite Element Buckling Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Mahfuz et al [94] performed a buckling test for three types of sandwich structures with the same face sheets but different foam core densities with embedded delamination at the interface. The results showed that the structure with the highest core density (the closest density to the face sheet density) had minimal delamination propagation.…”
Section: Spatial Gradient In Fgsmentioning
confidence: 99%